Augmentation of the lubricant heat transfer performance by exploiting the efficacy of Al2O3/ZnO hybrid nanoparticles as additives: An experimental analysis - Bipin Upadhaya; Rameshower Adhikari; Rabindra Prasad Dhakal; Amir Khanal; Surya Prasad Adhikari (Journal of Innovations in Engineering Education, 2024)
In the present study, merely emphasis on effect of Aluminum Oxide/Zinc Oxide Hybrid nanoparticle blended in the SAE 15W40 engine oil lubricant at two different concentration 0.1% and 0.01% by weight in thermal range of 330C to 880C, compared and investigated to normal engine oil thermophysical properties whilst soothe other tribological and rheological properties. First, Hybrid Nanoparticles has been prepared by solgel technique using previous research protocol and then subsequent prepared HNP has been undergoes characterization technique such as X-ray diffraction, UV-visible spectroscopy, FTIR spectroscopy, to ascertain the morphology of the synthesized samples and particles sizes. The prepared HNP has been blended with the lubricant using ultrasonication for yield Hybrid Nanofluid (HNF). Moreover, Zeta Potential Test has been conducted to determine the stability of the HNP within the host fluid engine oil. Again, FTIR spectroscopy, and UV-vis spectroscopy technique subsequent characterization technique has been employed using is utilized for the characterization of HNF, to define the morphology of the samples and particles sizes. The present research study explores increment on heat dissipation rate in an engine oil due to involvement of Aluminum Oxide/Zinc Oxide thereby reduction of cooling load by measuring the temperature differences experimentally and calculation of specific heat capacity analytically. Comparing pure engine oil with the HNP added at two different concentrations 0.1% and 0.01% wt in the engine oil revealed that the enhancement on the thermophysical properties of lubricants specifically Viscosity, Pour Point by 35.4% and 0.2% and, again engine performance testing between the normal and hybrid nanoparticle-based engine oil separately concluded that the average heat transfer rate on Hybrid Metal oxide-based Nano particle is higher than the normal base oil.